The mastery and uses of fire in antiquity - Rehder, J. E. (CEL - Canadian Publishers Collection., 2000)
Because pyrotechnology was considered a demeaning craft, there is very little about its practice in ancient texts; our knowledge of early developments is based almost entirely on interpretation of artifacts recovered by archaeology during the past century and a half. Literature in archaeology and anthropology, however, tends to concentrate on the artifact found rather than on how it was produced - on the pot or spearhead rather than the kiln or furnace. There is thus surprisingly little information on the practice and importance of pyrotechnology. The Mastery and Uses of Fire in Antiquity, written by an engineer with fifty years of experience in industrial research and pyrotechnology, rectifies this lack. J.E. Rehder covers the kinds of furnaces, the nature of the fuel used, and the productions created - fired clay, lime from limestone, metals from the reduction of ores, and glass from sand. He also shows convincingly that previous arguments that early deforestation resulted from furnace use cannot be supported. The Mastery and Uses of Fire in Antiquity provides much-needed information for anyone interested in archaeology, anthropology, and pyrotechnology.